PEMBELAJARAN BERBASIS SOFT SKILL UNTUK MAHASISWA ENTREPRENEURSHIP DENGAN MODEL KELOMPOK USAHA BERSAMA - Susandini, Aprilina; Faidal, Faidal (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2019)
Learning innovation is learning by using new ideas, methods and models toachieve learning goals. The Entreprenurship Study Program improves students' soft skillswith a joint business group model. Where this business group is used as a place ofpractice for students to apply the learning process in the classroom. The aim is toincrease student creativity in carrying out their business ideas. The implementation ofKUB model learning uses a qualitative approach, where data is obtained by means ofinterviews and observations. KUB will be managed by students, while lecturers superviseand provide direction.